Information Pyramids™: A New Approach to Visualising Large Hierarchies - Keith Andrews; Josef Wolte; Michael Pichler
This paper presents work in progress on a new technique for visualising and manipulating large hierarchies. The Information Pyramids approach compactly visualises hierarchical structures in three dimensions using pyramid-like structures, which grow upwards as the hierarchy is descended. The technique is described in the context of our early experience with a prototype file system visualiser based on Information Pyramids.
Late Breaking Hot Topic Paper